2014
DOI: 10.1021/ac403185a
|View full text |Cite
|
Sign up to set email alerts
|

Combine and Conquer: Surfactants, Solvents, and Chaotropes for Robust Mass Spectrometry Based Analyses of Membrane Proteins

Abstract: Mass spectrometry (MS) based proteomic technologies enable the identification and quantification of membrane proteins as well as their post-translational modifications. A prerequisite for their quantitative and reliable MS-based bottom-up analysis is the efficient digestion into peptides by proteases, though digestion of membrane proteins is typically challenging due to their inherent properties such as hydrophobicity. Here, we investigated the effect of eight commercially available MS-compatible surfactants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 21 publications
0
61
0
Order By: Relevance
“…This observation is in line with recent studies that showed a detergent-specific increase in the recovery of peptides mapping to membrane proteins derived from membrane fractions. 32,53 We were particularly interested in finding terms related to different membrane substructures in bacteria to infer whether there are consistent or different effects between the buffer systems between the species. Compared to human cells, which have a single phospholipid bilayer for compartmentation, the bacterial cell envelope contains an outer membrane that is separated from the inner membrane by the peptidoglycan cell wall that spans through the periplasmic space.…”
Section: Different Sample Preparation Strategies Enriched Specific Prmentioning
confidence: 99%
“…This observation is in line with recent studies that showed a detergent-specific increase in the recovery of peptides mapping to membrane proteins derived from membrane fractions. 32,53 We were particularly interested in finding terms related to different membrane substructures in bacteria to infer whether there are consistent or different effects between the buffer systems between the species. Compared to human cells, which have a single phospholipid bilayer for compartmentation, the bacterial cell envelope contains an outer membrane that is separated from the inner membrane by the peptidoglycan cell wall that spans through the periplasmic space.…”
Section: Different Sample Preparation Strategies Enriched Specific Prmentioning
confidence: 99%
“…Amphi-polymers (amphipols) can support protein extraction and digestion, but most aggregate below pH 3-4 and require removal pre-HPLC by precipitation and centrifugation (45), interrupting automatable workflow. Several recent studies compared numerous detergents for digestion, but most remained confined to industrial poly-disperse and ionic detergents that deactivated proteins and required removal; other attempts combined harsh detergents, organic solvents, high urea, high pressure, and high temperature (46).…”
Section: Figmentioning
confidence: 99%
“…However, although some of the methods provided good efficiencies for certain studies, Waas et al recently stated that the real deal would be the combination of surfactants, solvents, and chaotropes for robust MS-based identification of membrane proteins [37]. These authors tested a wide variety of organic solvents, chaotropic agents, surfactants, and their combinations.…”
Section: Organic Solvents and Detergent-free Buffersmentioning
confidence: 99%
“…These authors tested a wide variety of organic solvents, chaotropic agents, surfactants, and their combinations. Their data demonstrated that the inclusion of guanidine and acetonitrile in addition to surfactants maximized the overall digestion specificity, the total number of peptides, the average sequence coverage among all proteins, and the number of identified transmembrane domains [37].…”
Section: Organic Solvents and Detergent-free Buffersmentioning
confidence: 99%